The Youthful God revisited: Veiovis on Roman Republican denarii - Holman, Tyler (KOINON: The International Journal of Classical Numismatic Studies, 2019)
The identity of the deity depicted on the obverses of denarii issued by L. Caesius (112 or 111 BC), L. Julius Bursio (85 BC), Mn. Fonteius (85 BC), and Lucius Macer (84 BC) (Figures 1a-4b), along with a series of issues dated to 86 BC, has been the subject of inquiry among numismatists for at least 400 years. The primary candidates for the deity depicted on these coins have been Veiovis and Apollo, although some authorities have chosen to describe him as a syncretistic ‘Apollo-Veiovis,’ or opted for the conservative ‘Youthful God.’ Although the figure is clearly Apollonian, the identification is complicated by the addition of a thunderbolt being hurled, in the case of the Caesius issue, or being shown beneath the bust, in the case of the Fonteius issue. In order to attempt to address the accuracy of these interpretations it is necessary to trace the various identifications to their origins and to re-examine the coins in light of ancient literary and archaeological evidence.